Favorable morphoclimatic factors for the preservation of wetting organic carbon in mountain soils - Sardón Nina, Sandro (2021)
Humic substances (HS) are the main component of soil organic matter (SOM), a product of the pedogenetic process. In this study, the morphometric factors and climatic variable that condition the degree of humification, the organic carbon content of humic acids (HA) fulvic acids (FA) of 42 soil samples are related through the functional equation of factors of state of the soil proposed by Jenny. The degree of humification was determined by the Nagoya method proposed by Kumada. The quantification of organic carbon was determined using the method by Walkley and Black. The morphometric parameters of the relief were obtained from the Digital Elevation Model (DEM) and the climate parameter of the MODIS sensor. The results show that the relief factor conditions the degree of humification and the climate factor conditions the organic carbon content of humic acids (HA) and fulvic acids (FA).